HZ. PEYGAMBER’İN EVLENDİRDİĞİ KİŞİLER VE EVLENDİRİLMEAMAÇLARI - (:unkn) unknown (My University, 2017)
İslâm’da kutsal sayılan evlilik müessesesinin genel hedefi sağlam bir toplum oluşturmaktır.Bununla birlikte evliliğin nüfusun artması, meşru olmayan ilişkilerden uzak kalma, iffetikoruma, eşler arasında ünsiyet, akrabalık ve dostluk ilişkileri kurma veya geliştirme gibibirçok amaç ve faydaları da vardır. Hz. Peygamber’in kendi evliliklerinde bunlardanbazılarını uyguladığını görmekteyiz. Aynı şekilde başta beşerî amaç olmakla bazı amaçlardoğrultusunda hem kendi evlatlarını hem de ashaptan bazılarını evlendirmiştir. Resûl-iEkrem’in evlendirme amaçları içerisinde evliliğin teşviki veya evlilik konusunda tereddütedüşmüş kimselere yardım, ırkçılığın ortadan kaldırılması, dostluk bağlarının kurulması,akrabalık bağlarının kuvvetlendirilmesi ve himayenin ön plana çıktığının şahidi olmaktayız.

The general objective of the marriage institution, which is considered sacred in Islam, is to create a solid society. Apart from that, the marriage has many purposes and benefits such as increasing the population, staying away from illicit relations, protecting chastity, establishing a position among spouses, establishing kinship and friendship relations. We see the Prophet applying some of these features in their own marriage. Likewise, he has married some of his own sons and companions in the direction of some purposes, primarily for the purpose of humanity. In his marriage purposes, we are witnessing that marriage is promoted with the help of people who have hesitated about the promotion or marriage, the removal of racism and tribalism from the society, the establishment of friendship ties, protection of women.
THE PEOPLE WHO ARE GAVE MARRED BY THE PROPHET MUHAMMAD AND PURPOSES OF THEİR MARRİAGES